Incidence and impact of cardiac arrhythmias in coronavirus disease 2019 (COVID-19): A systematic review and meta-analysis (2020)
Background: Studies have shown that cardiac arrhythmias may occur in up to 44% of patients with severe coronavirus disease 2019 (COVID-19) and has been associated with an increased risk of death. This systematic review and meta-analysis aimed to evaluate the incidence of cardiac arrhythmias in patients with COVID-19 and their implications on patient prognosis. Methods: We performed a systematic literature search from PubMed, SCOPUS, Europe PMC, Cochrane Central Databases, and Google Scholar þ Preprint Servers. The primary endpoint of the study was poor outcomes including mortality, severe COVID-19, and the need for ICU care. Results: A total of 4 studies including 784 patients were analyzed. The incidence of arrhythmia in patients with COVID-19 was 19% (9e28%; I2 : 91.45). Arrhythmia occurred in 48% (38e57%; I2 : 48.08) of patients with poor outcome and 6% (1e12%; I2 : 85.33%) of patients without poor outcome. Patients with COVID-19 experiencing arrhythmia had an increased risk of poor outcome (RR 7.96 [3.77, 16.81], p < 0.001; I2 : 71.1%). The funnel-plot analysis showed an asymmetrical funnel plot with most of the studies on the right side of the effect estimate. The regression-based Egger’s test showed indication of small-study effects (p ¼ 0.001).